The Key Challenges for Islamic Fintech Implementation in Malaysia - Muhammad Ilyas bin Ab Razak; Nur Akma binti Mohd Dali; Muhammad Ilyas bin Ab Razak; Nur Akma binti Mohd Dali (Journal of Central Banking Law and Institutions, 2026)
This article explores the evolving landscape of Islamic fintech in Malaysia, delving into the looming regulatory challenges. As Malaysia solidifies its position as the global epicentre of Islamic finance and technological innovation, the intersection of these domains presents a distinctive set of challenges for regulators. The authors scrutinise the challenges and potential gaps within the regulatory framework governing Islamic fintech in Malaysia through meticulous analysis. The key challenges include ensuring Shariah compliance amid rapid technological advancements, addressing consumer protection concerns, navigating cross-border regulatory issues, managing technological risks and cybersecurity, achieving regulatory clarity for innovative models, and addressing talent scarcity and expertise gaps. Ultimately, the recommendations in this article offer valuable insights into developing regulatory models that harmonise innovation with adherence to Shariah principles. By embracing these recommendations, stakeholders in Malaysia can pave the way for a vibrant Islamic fintech ecosystem that thrives on innovation, integrity, and inclusivity. The study employs qualitative research techniques, including a review of existing literature, regulatory documents, and industry reports, to gather information on the regulatory framework governing the Islamic fintech ecosystem.